Analysis of Short-Term Steel Corrosion Products Formed in Tropical Marine Environments of Panama. (3rd September 2012) - Jaén, Juan A.; Iglesias, Josefina; Hernández, Cecilio
Abstract : A low-carbon steel A-36 and two conventional weathering steels A-588 and COR-420 exposed at four atmospheric test stations located in (i) Tocumen, an urban site near the Pacific Ocean, (ii) Sherman-Open, (iii) Sherman-Coastal, and (iv) Sherman-Breakwater on the Caribbean coast of Panama. Kinetics of the short-term atmospheric corrosion process and the relationship with exposure time and environmental characteristics of each site were investigated. The atmospheric exposure conditions, particularly the time of wetness, deposition of chloride, and the washing effect of contaminants on the metal surface by rain are of upmost importance in determining the corrosion behaviour and composition of rust. The corrosion products were mainly identified using room temperature and low temperature (80 K) Mössbauer spectroscopy, FTIR, and X-ray powder diffraction. In all samples, γ -FeOOH and α -FeOOH were the main constituents. Maghemite ( γ -Fe2 O3 ), magnetite (Fe3 O4 ), and Akaganeite ( β -FeOOH) were also identified.